Über die Diapause von Stenocranus minutus Fabr. (Homoptera: Auchenorrhyncha). (Zugleich 6. Beitrag zur Biologie mitteleuropäischer Zikaden). - Müller, Hans Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1957)
In a first analysis the hibernal arrest in the development of the female reproductive system of Stenocranus minutus Fabr. (Homoptera, Auchenorrhyncha, Delphacidae) is shown to be a praeoviposition diapause induced by long days (of 18 hours light and 6 hours darkness per day) during the larval period and terminated only by short days (8 hours light per day) during four weeks at the beginning of the adult stage. Short day periods (8/16) during the larval development yield a special modification (forma minutior) significantly smaller by 13% (male) respectively 18% (female) than normal specimens, the ovarial development of which takes place without any diapause. By that the young females are beginning to oviposit a few weeks after the last moult. The possible role of the humoral influences of the corpora allata on both rate and speed of development is discussed also with a view to morphogenesis and to the dynamic of populations.